Penafsiran tentang Pemakaian Jilbab menurut Pandangan Pemikiran Prof. KH M. Quraish Shihab - Siti Mu’awiyah Roni (An Nahdhoh Jurnal Kajian Islam Aswaja, 2021)
The interpreters of the Qur’an Quraish Shihab provide conclusions and interpretations that are different from most scholars in providing legal arguments about the veil. M. Quraish Shihab's opinion about the hijab is that it is not mandatory for Muslim women in Indonesia to wear the hijab. According to him, wearing the hijab is not a religious order. Because in religion it is not permissible for a syari'at to be based on religion without a clear argument. In ijtihad M. Quraish shihab seeks to use various approaches to ushul fiqh science, the most striking approach is the Ihtisan bi al-Urf approach, which prioritizes the customs and customs that develop in an area as legal objects, provided that these customs do not conflict with Islamic principles, anything contradicts the concept of Maqashid shari'ah. So according to the author, the Quraish Shihab indirectly states that the veil is a recommendation. (Tafsir al-misbah: 329-334).